2001
DOI: 10.1046/j.1365-2672.2001.01242.x
|View full text |Cite
|
Sign up to set email alerts
|

A colony blot immunoassay to detect enteroinvasive Escherichia coli and Shigella in water samples

Abstract: Aims: The aim of the study was to develop a colony blot immunoassay to detect Shigella and enteroinvasive Escherichia coli (EIEC) in water. Methods and Results: Spiked samples were ®ltered through nitrocellulose membranes. Colony prints on the ®lters were tested with a monoclonal antibody speci®c to IpaC, an antigen coded by the invasion plasmid of Shigella and EIEC. Invasive pathogens could be successfully detected with the technique, even in the presence of a large number of non-pathogenic bacterial cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The presence of faecal coliforms in water indicates contaminant per se, and may indicate that the sample is unsuitable for consumption, (Szakal et al, 2001). Ahmed et al, (2005) reported that the use of indicator bacteria such as faecal coliforms fc and Escherichia coli for the assessment of faecal pollution and possible water quality deterioration in various water sources is widely accepted concept in the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of faecal coliforms in water indicates contaminant per se, and may indicate that the sample is unsuitable for consumption, (Szakal et al, 2001). Ahmed et al, (2005) reported that the use of indicator bacteria such as faecal coliforms fc and Escherichia coli for the assessment of faecal pollution and possible water quality deterioration in various water sources is widely accepted concept in the world.…”
Section: Introductionmentioning
confidence: 99%
“…The role of food and water as vehicle for the transmission of this organism is well documented and represent a significant public health threat (Szakal et al, 2001). This study investigates the microbiological quality of water sources in Gusau municipal.…”
Section: Introductionmentioning
confidence: 99%
“…A protein A-alkaline phosphatase conjugate solution (Sigma) was diluted 1:500 in 2% casein and added to the blots for 1 h. The blots were washed again in TBS and developed with Naphthol/Fast red solution in 50 mM Tris-HCl, pH 8.0 (Sigma). This protocol was adapted from protocols described by Szakal et al (48).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, a simple colony blot technique, adapted from previous studies with Shigella (48), was used to demonstrate the surface expression of the CfaB and LTB proteins in SC608(pCFAI) and SC608(pC-FAI/LTB). This technique allows for the adsorption of extracellular proteins directly onto nitrocellulose for detection by immunoblotting.…”
Section: Methodsmentioning
confidence: 99%
“…They can detect only 10 5 ± 10 6 cells/mL without pre-enrichment. Methods such as the colony blot immunoassay [3] need a very high concentration of the bacterial colonies to be present on the membranes for the evaluation of the immuno reaction. To overcome these problems, alternative immunoassay techniques are being developed that aim at reducing the analysis time, simplifying the analysis procedure, improving sensitivity (to over 2000 times higher sensitivity than ELISA), while allowing their application to field conditions.…”
Section: Introductionmentioning
confidence: 99%